2020
DOI: 10.31234/osf.io/5zrqx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactance, morality, and disgust: The relationship between affective dispositions and compliance with official health recommendations during the COVID-19 pandemic.

Abstract: Emergency situations require individuals to make important changes in their behavior. In the case of the COVID-19 pandemic, official recommendations to slow the spread of the virus include costly behaviors such as self-quarantining, which individuals might be reluctant to adopt. However, whether or not people adopt those behaviors could make a huge difference in the impact of the pandemic. In this context, it is important to elucidate what psychological traits underlie people’s (lack of) compliance with offici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 14 publications
(15 reference statements)
7
40
2
Order By: Relevance
“…Notably, the effect sizes of the associations between germ aversion and preventative health behaviors were comparable to the effect sizes of the relations between COVID-19 concern and preventative health behaviors. These findings are consistent with recent work linking BIS indicators with COVID-19 related behavioral intentions and policy attitudes [14,15]. In general, these findings support theory suggesting the protective function of psychological diseaseavoidance mechanisms during a time of real disease threat [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, the effect sizes of the associations between germ aversion and preventative health behaviors were comparable to the effect sizes of the relations between COVID-19 concern and preventative health behaviors. These findings are consistent with recent work linking BIS indicators with COVID-19 related behavioral intentions and policy attitudes [14,15]. In general, these findings support theory suggesting the protective function of psychological diseaseavoidance mechanisms during a time of real disease threat [29].…”
Section: Discussionsupporting
confidence: 91%
“…As such, individuals higher in disgust sensitivity and germ aversion should be more concerned with the COVID-19 pandemic and more likely to engage in preventative health behaviors to avoid the disease. Some initial evidence supports this proposition, such that greater BIS reactivity has been linked to behavioral intentions and past efforts to follow COVID-19 health guidelines [14] and support for travel bans on Asian countries [15].…”
Section: Introductionmentioning
confidence: 98%
“…Aligning a message with the recipients' moral values facilitates persuasion (22) and increases their motivation to turn their intentions into actions (23). A previous study found that the best predictor of behavioral intentions, besides disgust, was how much participants cared about others (17). In line with these findings, recent research has found that framing COVID preventive measures as pro-social rather than selfinterested increased participants' intentions to adopt preventive behaviors (24).…”
Section: Introductionmentioning
confidence: 79%
“…Disgust-inducing videos showing nasal secretions on one's hand after sneezing are effective in promoting good handwashing practices (15) and viewing an infographic about infectious particles released during breathing and speaking by asymptomatic infected individuals increased knowledge about the effectiveness of masks (16). In a survey of the cognitive and motivational traits that predict compliance with official recommendations, disgust towards pathogens was one of the two best predictors of participants' behavioral intentions (e.g., intention to wash their hands) (17). To test the effect of the disgust lever, we used the following message: "When you touch something, your hands become covered with germs," with an image of cultures of germs from hands (for the Handwashing Poster) or "Don't let other people's viruses get close to you," with an image of the propagation of germs when someone coughs (for the Protective Behavior Poster).…”
Section: Introductionmentioning
confidence: 99%
“…All focus on the relationship between false beliefs and behaviors (or intentions to undertake behaviors). While some studies find associations between belief in misinformation and reduced self-protective behaviors (Allington et al, 2020;Banai et al, 2020;Bertin et al, 2020;Bierwiaczonek et al, 2020;Erceg et al, 2020;Sternisko et al, 2020;Swami & Barron, 2020;Teovanovic et al, 2020), others find no evidence of associations (Alper et al, 2020;Díaz & Cova, 2020). Still others find associations for some behaviors but not others (Imhoff & Lamberty, 2020;Pummerer & Sassenberg, 2020).…”
Section: Past Studiesmentioning
confidence: 99%